URGENSI PENGGUNAAN E-VOTTING DALAM SISTEM PEMILU DAN PILKADA SERENTAK 2024 DI KOTA SURABAYA - Reza Yuna Dwi Rahmawati; Sultoni Fikri (Jurnal Cakrawala Ilmiah, 2022)
The purpose of this study is to see the readiness of Surabaya City residents for the implementation of the E-Voting system in simultaneous elections and regional elections that will be held in 2024. This research uses an empirical approach with quantitative research methods and uses simple random sampling as a sampling technique. The focus of this research is to examine the readiness of Surabaya City residents regarding the implementation of e-voting systems in elections and regional elections in 2024 in Surabaya City. The results showed that the respondents in this study were dominated by young voters in the election (83.7%) who were active in the use of information and communication technology (100%). As many as 74.4% of respondents agree with the implementation of e-voting because it is efficient, effective, and practical. Regarding the obstacles that must be faced in the implementation of e-voting, Surabaya City is considered capable of overcoming considering adequate internet access and human resources that have a great opportunity in the successful implementation of the e-voting system, and must still be concerned about the security of the e-voting system. In addition, there is a need for a legal regulation that specifically regulates the implementation of e-voting considering that there is still a legal vacuum in its application.